Transformation of tobacco plants with virEl gene derived from Agrobacterium tumefaciens pTiA6 and its effect on crown gall tumor formation - Szegedi, E.; Oberschall, A.; Bottka, S.; Oláh, R.; Tinland, D. (International Journal of Horticultural Science, 2001)
The VirEl protein plays a key role in the transport of VirE2 protein from the bacterium to the plant cell during crown gall tumor induction by Agrobacterium. The virEl gene of A. tutnefaciens pTiA6 was cloned into the plant transformation vector pTd33 yielding pTd93virEl that was introduced into A. tuniefaciens EHA101 and used for tobacco transformation. The presence of the foreign DNA in the putative transgenic plants was confirmed by PCR analysis. Nine of the 41 transformed plants formed only small tumors following infection with the wild-type A. vitis octopine strain AB3. This property was inherited into the T1 generation. The expression of virEl gene in TI plants was demonstrated by Northern blot analysis.